2023
DOI: 10.1108/ijchm-04-2022-0437
|View full text |Cite
|
Sign up to set email alerts
|

Examining the negative relationship between length of stay at a hotel and customer satisfaction: evidence from online customer reviews

Abstract: Purpose Studies that investigate the length of stay as a predictor of consumer post-purchase behavior are rare despite its importance in efficient hotel management. By analyzing online customer reviews, this study aims to fill this gap in the extant literature on the relationship between length of stay and customer satisfaction level. Design/methodology/approach The authors collected and used online review data on hotels in London for this study. A series of linear regression analyses were conducted to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The literature suggests that length of stay (LOS) can moderate various aspects of guest experiences in the hospitality sector. Ben-Haobin et al (2021) found that LOS negatively moderates the link between customer mindfulness and brand experience, while Kim and Han (2023) observed a similar effect on customer satisfaction in London hotels. Inspired by these findings, we propose that LOS may also moderate the relationship between HSPs and brand identity.…”
Section: Moderating Role Of Length Of Staymentioning
confidence: 90%
See 2 more Smart Citations
“…The literature suggests that length of stay (LOS) can moderate various aspects of guest experiences in the hospitality sector. Ben-Haobin et al (2021) found that LOS negatively moderates the link between customer mindfulness and brand experience, while Kim and Han (2023) observed a similar effect on customer satisfaction in London hotels. Inspired by these findings, we propose that LOS may also moderate the relationship between HSPs and brand identity.…”
Section: Moderating Role Of Length Of Staymentioning
confidence: 90%
“…However, Ben-Haobin et al (2021) found a negative moderating influence of LOS on guest brand experience in 3 to 5-star hotels in Guangding Province, China. Similarly, Kim and Han (2023) noted negative direct effects of LOS on customer satisfaction in London high-end hotels suggesting that brand experience may decline as other factors become more pronounced.…”
Section: Structural Modelsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, a restaurant's menu choices can impact satiation by introducing new and exciting options, which can quickly become bored with the limited selection, resulting in a decline in interest and ultimately a satiation (Becerril-Castrillejo & Muñoz-Gallego, 2022). Satiation in the restaurant industry can have a significant impact on customers' switching intentions (Kim & Han, 2023). Customers who repeatedly dine at the same restaurant may lose enjoyment due to satiation and seek new dining options as novelty and excitement wear off, rekindling their enthusiasm (Yan et al, 2019).…”
Section: Satiation and Switching Intentionsmentioning
confidence: 99%